Isolation of Human Fibrinogen and its Derivatives by Affinity Chromatography on Gly-Pro-Arg-Pro-Lys-Fractogel - Kuyas, C; Haeberli, A; Walder, P; Straub, P W (Thrombosis and Haemostasis, 1990)
With an immobilized synthetic pentapeptide GlyProArgProLys comprising the N-terminal sequence GlyProArg of the α-chain of fibrin, a new affinity method for the quantitative isolation of fibrinogen out of anticoagulated plasma was developed. The method proved to be superior to all known isolation methods in respect to ease of use and yield, since fibrinogen could be isolated in one step out of plasma with a recovery of more than 95% when compared to the immunologically measurable amounts of fibrinogen. Moreover the amounts of contaminating proteins such as fibronectin, factor XIII or plasminogen were negligible and the purity of the isolated fibrinogen was higher than 95% as measured by polyacrylamide gel electrophoresis. The clottability was 90% and more. Another advantage of this affinity purification method is the possibility to isolate fibrinogen quantitatively out of small plasma samples (<5 ml). Further, abnormal fibrinogen molecules, provided their complementary binding site for GlyProArg is preserved, may also be quantitatively isolated independent of any solubility differences as compared to normal fibrinogen. In addition fibrin(ogcn) fragments originating from plasmic digestion can be separated on the basis of their affinity to GlyProArg. The described affinity gel can be used more than 50 times without any loss of capacity.